Natural-scientific aspects of the marginalist revolution - D. G. Mudrik; V. N. Kovnir (Russian Journal of Economics and Law)
Objective: to define the basic principles of the new paradigm, put forward by the founders of marginalism (Gossen, Jevons, Menger, Walras), and its connection with the natural science paradigm; to study the marginalist revolution as a transition of economics from a moral (idealistic) worldview, based on anthropomorphism, teleologism and hierarchism, to a natural-scientific (naturalistic) worldview, based on empiricism and rationalism.Methods: historical-genetic method, philosophical-dialectical method, natural-scientific method of interdisciplinary analysis.Results: the article presents the main stages of the birth of natural-scientific ideas in the works by classical school authors and their further development. The author analyzes the emergence of the natural-scientific method in the cognition of natural phenomena in the 17th century and its further application in the cognition of economic phenomena in the works by classical school predecessors and marginalists. The revolutionary ideas of the marginalism founders are proved to continue the natural-scientific revolution in economics. The latter was based on empirical (sensory) cognition of the connection between the perception of the subjective value of goods and their observed natural properties (usefulness) and rarity. This received a rational mathematical expression in the form of the “law of marginal utility”. The author identified the main philosophical and methodological problems that prevent marginalists from developing scientific ideas in economics, related to the existing dichotomy in the cognition of material and spiritual phenomena, leading to difficulties in the scientific explanation of goods value. As an attempt to overcome these contradictions, economic phenomena began to be explained by a mathematical model of “rational” human behavior based on the general postulates of an “economic person’s” behavior or rules and institutions established by society.Scientific novelty: it was shown that the subjective sensory perception of the goods value can be studied as objectively as the subjective sensations of the objects’ natural properties. The method of economic activity research proposed by marginalists allows giving natural scientific definitions of force and energy in economic processes. This makes them not just “convenient” metaphors, but also tools that help to penetrate into the essence of economic processes.Practical significance: the provisions and conclusions of the article substantiate and expand the application of the natural science method in the analysis and modeling of economic processes.The article is based on the report by D. G. Mudrik and V. N. Kovnir “The Unfinished Marginalist Revolution”, presented at the 5th Russian Economic Congress in Yekaterinburg on September 11–15, 2023 (pp. 59–62). http://www.econorus.org/pdf/Volume1_REC-2023.pdf